Visioning Together: A Tool for Successful Co-Creation of Learning Environments - Michelle Chavey; Mackenzie Cox (Educational Considerations, 2025)
This qualitative research study explores the use of a new belief-based visioning tool as a component of co-creating new learning environments. It examines the perceptions of educators from a Midwestern suburban school district working with an architectural firm to design a new middle school. The study was designed as a participatory evaluative case study, with data collected through interviews, focus group discussions, documentation, and observation of the design process during co-creation meetings between the designers and the educators. Findings demonstrate the merit of the belief-based visioning tool and its resulting Learning Belief Statements. The tool was found to be valuable to the educators who crafted the vision, as well as to the designers who used the final Learning Belief Statements throughout the design process. The tool’s impact has implications not only for designers and educators interested in implementing a co-creation process to design successful learning environments, but also for leaders and administrators seeking to strengthen staff culture across a building or district.
Keywords: Educational leadership; co-creation; learning environments; school vision; visioning; school culture; learning spaces; teacher leadership